DUKUNGAN KELUARGA DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KECEMASAN PASIEN HEMODIALISA - Mori Agustina br Perangin-angin; Cia Putri Silaban (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
According to Riskesdas data the highest cause of death by non-communicable diseases in Indonesia is chronic kidney disease (CKD), for CKD patients who have to undergo hemodialysis therapy for the rest of their lives must be very heavy to experience and often feel anxiety to decreased physical activity and quality of life. This research aimed to discover the effect of family support on the anxiety level of hemodialysis patients. This research was a quantitative research with used a descriptive correlation research method and used a purposive sampling technique. The number of samples was 81 respondents who were hemodialysis patients at Rumah Sakit Advent Bandar Lampung. The data collection was conducted in February 2020. To determine family support, the Family Support Scale (FSS) was used and the Hospital Anxiety and Depression Scale (HADS) were used to measure the level of anxiety. Simple linear regression test results obtained a significant value of p 0.015 < 0.05 that means Ho rejected and Ha accepted. In conclusion, there is an effect of family support on the level of anxiety of hemodialysis patients at Rumah Sakit Advent Bandar Lampung. The authors has suggested that the families to more spirit to providing support patients in undergoing hemodialysis.